Այգու հողամշակ ֆրեզ-մեքենայի արտաշարժ բանող օրգանի կառավարմանէլեկտրական սխեմայի մշակում - Հարությունյան, Գևորգ (ՀԱԱՀ հիմնադրամ)
Согласно исследованиям и наблюдениям, при работе некоторых фрезерных машин повреждаются ствол и корневая система деревьев, отклоненных от прямолинейности ряда. Следовательно, была разработана новая система управления выносным рабочим органом. Существующая система дополнена реле, а механические контакты заменены на индуктивные датчики, что позволяет минимизировать гистерезис, возникающий при электромеханическом контакте. В то же время было разработано соленоидное электроклапанное устройство для управления потоком масла. Предлагаемая система позволяет фиксировать рабочий орган в регулируемых промежуточных положениях и поддерживать заданную агротехническими требованиями ширину зоны защиты растений. This article focuses on optimizing the operation of a tillage machine equipped with a movable working body (tiller). Observations have shown that the current design of the machine can damage tree trunks and root systems, particularly when trees deviate from the linear arrangement of planting rows. This damage occurs because the machine fails to maintain the plant protection zone required by agricultural standards. To address this issue, an electrical control system has been developed that enables the working body to be fixed in adjustable intermediate positions, thereby eliminating the above-mentioned drawback. Specifically, an electric valve device with a solenoid coil has been integrated into the hydraulic control system to regulate oil flow. Inductive sensors were selected to detect the position of the working body, ensuring signal transmission from the sensor rod to the control unit with minimal delay and hysteresis.
Keywords: Ագրարային ճարտարագիտություն